Cultivation of Oyster Mushroom: A Sustainable Approach of Rural Development in Nepal - Pokhrel, Chandra P. (Journal of Institute of Science and Technology, 2016)
This study attempts to investigate the easily acceptable and low cost technology of Oyster mushroom cultivation. Locally and easily available substrates such as corn cob, vegetable residue and waste paper were examined with the supplementation of rice bran and chicken manure separately. During the study mycelial growth, spawn run, pin head formation, yield and biological efficiency were observed. Best mycelial extension, early pin head formation and better yield were observed in corn cob substrate followed by paper waste and vegetable residue. Among the substrates used, corn cob showed the highest yield with range from 99.08 to 109.50 % biological efficiency, whereas 69.81 to 88.36 % and 52.26 to 65.22 % biological efficiency was observed in paper waste and vegetable residue respectively. Rice bran was the best supplement for the promotion of growth and development of Oyster mushroom. Journal of Institute of Science and Technology Vol. 21, No. 1, 2016, page:56-60